NETWORK COOPERATIVES AND THE REDUCTION OF OPPORTUNISM IN THE AGRIBUSINESS SEGMENT: A SYSTEMATIC BIBLIOGRAPHIC REVIEW - Aguiar, Leandro Guedes [UNESP]; Pigatto, Giuliana Santini [UNESP]; Bernardo, Cristiane Hengler [UNESP]; Morales, Angelica Gois [UNESP] (Inst Federal Educacao, Ciencia & Tecnologia Sao Paulo, 2020)
The Brazilian citrus industry has been the focus of in-depth scientific research in the 21st century, mainly due to the peculiarities of the coordination of this agro-industrial system, in which the cooperatives' performance and network format are highlighted. This represents an alternative to the well-known process of reduction of small citrus producers, as well as support in mitigating opportunism in transactions. In this context, the objective of this article is to carry out a systematic review of the literature on the topic of cooperatives that use a network format and the reduction of opportunism applied to the agribusiness segment in Brazil and worldwide. As a result, the importance of networked agro-industrial cooperatives to reducing opportunism in economic transactions is attested in all the researched articles, as is the lack of empirical academic studies to enrich and make the researched literature more robust.
Keywords: governance; network; systematic review of the literature; citriculture; cooperative